2018
DOI: 10.1155/2018/5738090
|View full text |Cite
|
Sign up to set email alerts
|

Numerical Investigation on Head and Brain Injuries Caused by Windshield Impact on Riders Using Electric Self-Balancing Scooters

Abstract: To investigate head-brain injuries caused by windshield impact on riders using electric self-balancing scooters (ESS). Numerical vehicle ESS crash scenarios are constructed by combining the finite element (FE) vehicle model and multibody scooter/rider models. Impact kinematic postures of the head-windshield contact under various impact conditions are captured. Then, the processes during head-windshield contact are reconstructed using validated FE head/laminated windshield models to assess the severity of brain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 35 publications
(50 reference statements)
0
8
0
Order By: Relevance
“…This has led to a dilemma of where scooter riders should be as they have the potential to seriously injure pedestrians in collisions, but on the road riders are relatively unprotected as compared with vehicle passengers. 13 18 This continues to be a challenging issue to address, especially when considering results of a recent study reporting e-scooter riders are more likely to engage in more risky behaviors than pedestrians and cyclists. 19 …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This has led to a dilemma of where scooter riders should be as they have the potential to seriously injure pedestrians in collisions, but on the road riders are relatively unprotected as compared with vehicle passengers. 13 18 This continues to be a challenging issue to address, especially when considering results of a recent study reporting e-scooter riders are more likely to engage in more risky behaviors than pedestrians and cyclists. 19 …”
Section: Introductionmentioning
confidence: 99%
“…Recently, a handful of studies have reported on e-scooter related injuries in the emergency department setting with a focus on the low helmet use-reported at <5%-and the broad spectrum of injuries patients have been experiencing from minor soft tissue injuries to traumatic brain injuries. [13][14][15][16][17] In addition to rising rates of scooter riders experiencing injuries, injury rates of pedestrians sharing the sidewalk with scooter riders have also increased. This has led to a dilemma of where scooter riders should be as they have the potential to seriously injure pedestrians in collisions, but on the road riders are relatively unprotected as compared with vehicle passengers.…”
Section: Introductionmentioning
confidence: 99%
“…Better windshield and engine hood models should be considered as well. [47][48][49][50][51] Consideration of these factors mentioned above might produce more reliable results, which is a very noteworthy content of further research.…”
Section: Discussionmentioning
confidence: 99%
“…Xu et al [7] used MADYMO multi-rigid body analysis software to analyse the severity of head injuries of ESS riders, cyclists and pedestrians in side-collision scenarios and found that the ESS riders' risk of head injury was less than that of pedestrians. Shang et al [8] used a multi-body (MB) and finite-element (FE) method to analyse the injury due to the collision between ESS riders' head and car windshield through the reconstruction of ESS collision accident; their results showed that the severity of riders' head injury had a significant relationship with head linear velocity, angular velocity and collision position. Xu et al [9] used the same method to conduct an in-depth study on the injury due to the collision between the head of ESS riders and the road surface, and the results showed that the risk of head injury positively correlated with speed.…”
Section: Introductionmentioning
confidence: 99%
“…Shang et al . [8] used a multi-body (MB) and finite-element (FE) method to analyse the injury due to the collision between ESS riders' head and car windshield through the reconstruction of ESS collision accident; their results showed that the severity of riders’ head injury had a significant relationship with head linear velocity, angular velocity and collision position. Xu et al .…”
Section: Introductionmentioning
confidence: 99%